(3GdHhQUGJ hGdCShGb GdeGdjI OhQ GdefXeGJ hGdJcJdGJ GdOhdjI hGdCgdjIs - (3UdGM GdOjf MSf(B, (3GdSjSjs ((3GdbGgQI(B:s (3OGQ GdcJGH GdMOjK(B,s, 2014)
(3GdefXeGJ GdEbJUGOjI GdOhdjI hGdEbdjejI(B- (3GdHhQUGJ hGdCShGb GdeGdjI GdOhdjIs
(3GdeQGLY U(B.187s
Keywords: (3GdCShGb GdeGdjIs; (3GdHhQUGJs; (3GdefXeGJ GdOhdjIs